Calculation Method of Transmission System Time Between Overhaul with Considering Running Time - Wenbin Pan; Weizhen Liu; Huaipeng Li (Jixie chuandong)
By establishing the mathematical model of helicopter transmission system running time and flight time, engine working time, the time ratio relation between running time and flight time is deduced, that is, conversion coefficient. Using Minitab software to complete the data calculation, the running time of the transmission system is converted into the corresponding flight time. Compared with the traditional way which only considers the flight time in the air, the real and accurate time between overhaul can be obtained and the reliability can be improved. At the same time, the maintenance time scale of the transmission system and other parts of the helicopter can be ensured. This method is successfully applied to a certain type of helicopter, and some reference for the maintenance of similar aviation products can be provided.